2013
DOI: 10.1002/cam4.75
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact and the relevance of PTEN copy number alterations in patients with advanced colorectal cancer (CRC) receiving bevacizumab

Abstract: Loss of phosphatase and tensin homologue (PTEN) expression may be prognostic in colorectal cancer (CRC) and may have a correlation with vascular endothelial growth factor (VEGF) expression via hypoxia-inducible factor 1 (HIF-1) alpha, and the PI3K/mTOR pathways. We therefore have explored the prognostic association of PTEN loss and the potential that PTEN loss may be predictive of outcome with bevacizumab. Patients enrolled in the AGITG MAX trial, a randomized Phase III trial of capecitabine (C) +/− bevacizuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
0
23
1
Order By: Relevance
“…PIK3CA (phosphoinositide‐3‐kinase, catalytic, alpha) mutations were found in a higher number of patients with lung metastases (20%) and brain metastases (23.9%) versus those with liver metastases (7.7%) . Patients with phosphatase and tensin homolog (PTEN) loss had less lung metastases . Higher levels of thymidylate synthase gene expression were noted in patients with pulmonary versus liver metastases .…”
Section: Discussionmentioning
confidence: 99%
“…PIK3CA (phosphoinositide‐3‐kinase, catalytic, alpha) mutations were found in a higher number of patients with lung metastases (20%) and brain metastases (23.9%) versus those with liver metastases (7.7%) . Patients with phosphatase and tensin homolog (PTEN) loss had less lung metastases . Higher levels of thymidylate synthase gene expression were noted in patients with pulmonary versus liver metastases .…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of PTEN (10q) has been found without significant association with the outcome of CRC patients who received antivascular endothelial growth factor therapy, 121 although the PTEN gene is a well-established tumor suppressor. Instead, deletions on 10p15.3-p14 seem to associate with poor prognosis.…”
Section: Chr10mentioning
confidence: 99%
“…[91][92][93] Regarding response to EGFR-targeted therapies, several studies have shown an association with PTEN loss and lack of response to cetuximab and panitumumab. [94][95][96][97] However, other published studies failed to demonstrate a clear correlation between loss of PTEN expression and response to anti-EGFR therapy.…”
mentioning
confidence: 99%